2016
DOI: 10.1007/s10995-016-2069-y
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Charley Exposure and Hazard of Preterm Delivery, Florida 2004

Abstract: Objective Hurricanes are powerful tropical storm systems with high winds which influence many health effects. Few studies have examined whether hurricane exposure is associated with preterm delivery. We aimed to estimate associations between maternal hurricane exposure and hazard of preterm delivery. Methods We used data on 342,942 singleton births from Florida Vital Statistics Records 2004-2005 to capture pregnancies at risk of delivery during the 2004 hurricane season. Maternal exposure to Hurricane Charley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…These findings are consistent with other studies, which did not find a significant effect of exposure to natural disasters on preterm birth and low birth weight. 1,2,28,29,[32][33][34] Our findings differ from prior research evidence published by Simeonova, and highlight disparities in the literature regarding the influence of tornadoes on preterm birth and low birth weight. Simeonova detected marginal statistically significant evidence correlating exposure to thunderstorms, hurricanes, and tornadoes with preterm birth and low birth weight.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with other studies, which did not find a significant effect of exposure to natural disasters on preterm birth and low birth weight. 1,2,28,29,[32][33][34] Our findings differ from prior research evidence published by Simeonova, and highlight disparities in the literature regarding the influence of tornadoes on preterm birth and low birth weight. Simeonova detected marginal statistically significant evidence correlating exposure to thunderstorms, hurricanes, and tornadoes with preterm birth and low birth weight.…”
Section: Discussioncontrasting
confidence: 94%
“…[1][2][3] Adverse pregnancy outcomes associated with in utero exposure to severe storms include low birth weight, preterm birth, and small for gestational age. [1][2][3] Research evidence shows that the magnitude of the effects of various natural disasters tends to vary by the disaster type and exposure experience. 3 Little is known about birth outcomes related to prenatal exposure to tornadoes.…”
mentioning
confidence: 99%
“…82 Physical health 16 articles focused on physical health after multiple disasters. 75,76,79,80,[122][123][124][125][126][127][128][129][130][131][132][133] One study, which looked at 500 com munities across the USA, found that those who had experienced recurring disasters had increased incidences of asthma, high blood pressure, and self-reported poor mental health and poor physical health. Moreover, the incidence of all such outcomes increased with each additional year in which a community experienced a disaster.…”
Section: Reviewmentioning
confidence: 99%
“…One article on maternal and child health found that exposure to Hurricane Charley (2004) during pregnancy or shortly before conception was associated with increased risk of extremely preterm delivery; however, exposure to additional hurricanes did not seem to increase this risk further. 80 There were also indications of a connection between mental health and physical health outcomes in settings affected by multiple disasters. One study in the Gulf Coast of the USA suggested that losses as a result of Hurricane Katrina were associated with subsequent distress related to the Deepwater Horizon oil spill, which in turn was associated with physical health symptoms-suggesting that mental health effects from disasters can be one pathway to physical health effects.…”
Section: Reviewmentioning
confidence: 99%
“…Pregnant women who are at risk of contracting the flu and suffering from its complications are now also at risk for psychological consequences associated with the COVID-19 pandemic [32] , [33] , [34] , [35] , [36] , [37] , [38] . Therefore, the present study sought to examine the factors influencing compliance with the influenza vaccine among pregnant and postpartum women in the shadow of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%